DESCRIPTION OF STUDENTS’ MATHEMATICS PROBLEM SOLVING RELATION IN CONCEPTS UNDERSTANDNG FROM EVALUATED LEARNING STYLES AT CLASS VIII SMPN 4 BINAMU JENEPONTO DISTRICT - Syaharuddin S (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2019)
The research is descriptive quantitative-qualitative approach. Quantitative approach used in analyzing how the relationship between problem-solving skills with students' understanding of the concept. While the qualitative approach used in describing how the problem-solving skills class VIII SMP Negeri 4 Binamu Jeneponto in relation to understanding the concept in terms of learning styles. This study, data were collected through the initial observation, the provision of learning styles questionnaire, test understanding of concepts, and problem-solving ability tests and structured interviews. Data were analyzed using Chi Square analyze the association between mathematical problem solving skills with an understanding of the concept in terms of students' learning styles. The results showed that there is an association between the ability of solving math problems with understanding the concept of student stylish visual learning the value of χ2 count = 21,000 and significance (Asymp. Sig. (2-sided)) = 0.000 and there is an association between the ability of solving mathematical problems with the understanding of the concept auditory learning style student with χ2 value and significance count = 17.967 (Asymp. Sig. (2-sided)) = 0.000. Students with visual and auditory learning style can solve the problems SPLDV given by the troubleshooting steps Polya because it may be posisible students have an understanding of the SPLDV.